A randomised controlled trial of sensory awareness training and additional motor practice for learning scalpel skills in podiatry students. Issue 1 (December 2016) - Causby, Ryan; McDonnell, Michelle; Reed, Lloyd; Hillier, Susan
Abstract Background The process of using a scalpel, like all other motor activities, is dependent upon the successful integration of afferent (sensory), cognitive and efferent (motor) processes. During learning of these skills, even if motor practice is carefully monitored there is still an inherent risk involved. It is also possible that this strategy could reinforce high levels of anxiety experienced by the student and affect student self-efficacy, causing detrimental effects on motor learning. An alternative training strategy could be through targeting sensory rather than motor processes. Methods Second year podiatry students who were about to commence learning scalpel skills were recruited. Participants were randomly allocated into sensory awareness training (Sensory), additional motor practice (Motor) or usual teaching only (Control) groups. Participants were then evaluated on psychological measures (Intrinsic Motivation Inventory) and dexterity measures (Purdue Pegboard, Grooved Pegboard Test and a grip-lift task). Results A total of 44 participants were included in the study. There were no baseline differences or significant differences between the three groups over time on the Perceived Competence, Effort/ Importance or Pressure/ Tension, psychological measures. All groups showed a significant increase in Perceived Competence over time (F1, 41 = 13.796, p = 0.001). Only one variable for the grip-lift task (Preload Duration for the non-dominant hand) showed a significant difference over time between the groups (F2, 41 = 3.280, p = 0.038), specifically, Motor and Control groups. Conclusions The use of sensory awareness training, or additional motor practice did not provide a more effective alternative compared with usual teaching. Further research may be warranted using more engaged training, provision of supervision and greater participant numbers. Trial registration Australian New Zealand Clinical Trials Registry (ANZCTR):ACTRN12616001428459 . Registered 13th October 2016. Registered Retrospectively.